Apert Syndrome: Outcomes From the Australian Craniofacial Unit's Birth to Maturity Management Protocol. Issue 5 (July 2016) - David, David J.; Anderson, Peter; Flapper, Walter; Syme-Grant, Jonathan; Santoreneos, Steven; Moore, Mark
Abstract : Abstract: The complex, progressive, multisystem nature of Apert syndrome presents many challenges to managing surgeons. Based on the pioneering work of Paul Tessier, the senior author developed a multidisciplinary birth to maturity management protocol for Apert syndrome. Between 1975 and 2014 the Australian Craniofacial Unit has treated 174 Apert syndrome patients and 28 have completed full protocol management. This paper reviews the scientific contribution made to the management of Apert syndrome by the Australian Craniofacial Unit, the development and evolution of the protocol and presents comprehensive data on the surgical and nonsurgical craniofacial interventions, and outcomes for the 28 patients who have completed the programme; 26 had normal visual acuity, 22 had normal hearing, 20 achieved normal or nearly normal speech, 24 a functional class I occlusion, 18 completed mainstream schooling of whom at least 8 went on to tertiary education, at least 13 gained employment and 15 developed good social groups. These outcomes equal or exceed those presented by other authors and provide compelling evidence of the value of protocol management in clinical outcomes, in addition to their value in international collaboration, and scientific development of future therapeutic strategies for the management of Apert syndrome.